The next one : biografi Dahlan Iskan / Budi Rahman Hakim, M. Deden Ridwan ; penyunting, A. Fathoni, Alfi Rahmadi, M. Benicia - Budi Rahman Hakim, ; Deden Ridwan, M., ; Fathoni, A. ; Alfi Rahmadi ; Benicia, M. (Arsy Publishing, 2014)
xvii, 749 hlm. : ilus. ; 24 cm.